UJI VIGOR GULMA ECHINOCHLOA CRUS-GALLI TERHADAP BERBAGAI ALELOPATI TUMBUHAN - Risvan Anwar; Eka Suzanna (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2012)
This research aims to test vigor Echinochloa crus-galli weeds toward seven species of plants which are known have alelopati potential as herbicide vegetation to reduce vigor Echinochloa crus-galli weeds. This research was conducted in laboratorium Balai Proteksi Tanaman Perkebunan of Bengkulu Province, which started from January to March 2011. The method of this research was Completely Randomized Design (CRD) with single factor that was alelopaty extract treatment which was done as follow: Control (with aquadestilata), Bermuda Grass (Cynodan dactylon), Corn (Zea mays), Sapphire (Pogosthemon cablin), Pinus (Pinus spp), Teki Grass (Cyperus rotundus), Saegegrass (Imperata cylindrica), Jarak Plant (Jatropha curcas). Each treatment was repeated five times. The result of the test showed that alelopaty treatment was significantly influenced the decreasing of vigor Echinochloa crus- galli weeds. Alelopati of Bermuda Grass (Cynodan dactylon), Corn (Zea mays), Sapphire (Pogosthemon cablin), Pinus (Pinus spp), Teki Grass (Cyperus rotundus), Saegegrass (Imperata cylindrica), Jarak Plant (Jatropha curcas) were able to reduce vigor Echinochloa crus-galli weeds.